Multi-target mechanism of Physalis angulata to treat malaria based on network pharmacology and molecular docking - Indradi, Raden Bayu; Muhaimin, Muhaimin; Barliana, Melisa Intan; Khatib, Alfi; Maisyarah, Intan Timur; Pitaloka, Dian Ayu Eka; Pratomo, Muhammad Fadhil (Elsevier, 2025)
Introduction: Antimalarial drug resistance, such as artemisinin partial resistance, has become a major concern in malaria eradication. Thus, the development of new alternatives for malaria treatment is needed. Medicinal plants used by people in endemic areas, such as Physalis angulata, need to be studied for their claimed efficacy to treat malaria. Methods: In this study, we used a network pharmacology approach utilising several databases (KNApSAck, GeneCards, SwissADME, Pharmmapper, SwissTargetPrediction, SuperPred, STRING-DB, DAVID) to predict the multi-mechanism of P. angulata to alleviate malaria, as confirmed by molecular docking. Results: The result revealed that 25 compounds of P. angulata interact with 22 malaria-related targets, where molecular docking performed for compounds and targets associated with malaria pathways verified that with angulatin F showed a good binding affinity with ICAM1, VCAM1, and SELE, physagulin A with IL1B, physagulin J with TNF, and physalin V with TLR4. Conclusion: We predict that P. angulata alleviates malaria through several mechanisms, primarily by regulating the inflammatory response. This mechanism reduces excess proinflammatory cytokines like TNF and IL1B, leads to reduced levels of adhesion molecules, and ultimately reduces or prevents the severity of malaria.